2014
DOI: 10.1097/mpg.0000000000000296
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Adequacy of Standard Supplementation in Preterm Neonates From South India

Abstract: The prevalence of VDI was not high at birth; however, a large proportion of preterm babies were vitamin D insufficient at 6 weeks despite being supplemented with vitamin D 400 IU/day. The recommended vitamin D supplementation of 400 IU appears to be inadequate to prevent VDI, and hence randomized controlled trials looking at higher doses of vitamin D supplementation are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
7
2
Order By: Relevance
“…In the present study, 98.9% of preterm infants had vitamin D insufficiency or deficiency, and 51.1% of preterm infants were severely vitamin D deficient. These results showed much lower 25-OHD concentrations compared to those reported in previous studies of preterm infants 13 14 15 16 17 18) , and also were lower than those in previous reports on Korean newborns 3 19 20) . Although almost all infants had vitamin D insufficiency or deficiency, the serum concentrations of calcium, phosphorous and ALP at birth were maintained within the normal range.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In the present study, 98.9% of preterm infants had vitamin D insufficiency or deficiency, and 51.1% of preterm infants were severely vitamin D deficient. These results showed much lower 25-OHD concentrations compared to those reported in previous studies of preterm infants 13 14 15 16 17 18) , and also were lower than those in previous reports on Korean newborns 3 19 20) . Although almost all infants had vitamin D insufficiency or deficiency, the serum concentrations of calcium, phosphorous and ALP at birth were maintained within the normal range.…”
Section: Discussioncontrasting
confidence: 79%
“…Our study reports the lowest 25-OHD concentrations of preterm infants published to date, as far as we have been able to determine. The previous studies involved preterm infants with younger gestational age compared to that in the present study 13 14 15 16 17 18) , but the 25-OHD concentrations were much higher than those of preterm infants in the present study. The 25-OHD concentrations were even lower than those of infants in Northern European countries including Norway (12.2±5.5 ng/mL) 23) , and Finland (11.7±4.7 ng/mL) 24) .…”
Section: Discussioncontrasting
confidence: 61%
“…Tergesti et al also reported no improvement in vitamin D deficiency with supplementation at 400 IU daily. In fact, the percentage of VDD was 12.6% at birth and it increased to 52.2% at 6 weeks [11]. In a recently published randomized doubled-blind controlled trial comparing the effect of vitamin D supplementation at 400 vs. 1000 IU daily in a group of preterm neonate at 24 to 27 weeks gestation, mean 25OHD concentration increased from 21.3 ng/mL to 47.5 ng/mL at 40 weeks CGA in the 1000 IU daily group, but mean 25OHD concentration in 400 IU daily group decreased from 31.3ng/mL to 17.5 ng/mL.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, premature infants are at risk for vitamin D deficiency . And several studies have suggested this finding . Ataseven et al investigated vitamin D levels of 152 infants born 29–35 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in animal studies it has been demonstrated that vitamin D improves lung structure after hyperoxia‐induced lung injury and intra‐amniotic endotoxin exposure . Preterm infants have risks of developing vitamin D deficiency and BPD compared with that of full‐term infants . Recommendations for daily vitamin D intake is miscellaneous .…”
Section: Introductionmentioning
confidence: 99%